Visual Arts and Science - Opportunities and Limitations of Their Integration in the First Cycle of Primary Education - Vera D. Večanski; Sanja R. Blagdanić; Marija M. Pavlović (University of Belgrade, Teacher Education Faculty, 2020)
Integrative teaching is based on the wholeness of the reality that surrounds us and, consequently, on a holistic approach to school subjects. As such, it involves not only linking the content, but also the processes and procedures, as well as the actors in education, for the purpose of achieving the common goal and the individual goals of the teaching disciplines involved in the process. In the last few decades, different educational concepts based on the integration of the visual arts and sciences have particularly attracted attention. Although these areas appear to be completely different in terms of content and methodology, they share a common starting point in the child's natural curiosity, sensory cognition and research activities. Given that teaching in Serbia is subject-based, we wanted to examine whether teachers in Serbia manage to integrate the subjects Fine Arts and Science and Social Studies when they teach the properties of materials as one of the points of intersection of these areas. The results obtained by combining a systematic observation of ten art classes and interviews with teachers show that they do not clearly identify and use the opportunities for integrative study of the teaching content of these two school subjects. Such findings indicate that there is a need to train teachers to apply methodological strategies that support integrative approaches, both during the initial education of the pre-service primary school teachers and later on, in the course of their professional development.